Reactive Power Markets: A Review - Thomas Wolgast; Stephan Ferenz; Astrid NieBe (IEEE Access, 2022)
Liberalization of the energy system sets the way towards market-based solutions for ancillary service provision. Local reactive power markets are envisioned to achieve more economically and technically efficient reactive power provision to solve voltage control problems in future distribution and transmission grids. However, market-based reactive power procurement is a difficult and yet unsolved problem. This survey provides a comprehensive overview of the characteristics and hardships of reactive power markets. That is followed by a literature overview of reactive power market design, including local markets and markets on system operator level. Further, methods how to analyse reactive power markets are discussed, focusing on market power, game theoretical approaches, Reinforcement Learning, and manipulation of reactive power markets. From this overview, trends and current research gaps are derived and some general research recommendations are given to serve as a guideline for future research in the field of reactive power markets.